If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(z + 3) = 5(z + -8) Reorder the terms: 10(3 + z) = 5(z + -8) (3 * 10 + z * 10) = 5(z + -8) (30 + 10z) = 5(z + -8) Reorder the terms: 30 + 10z = 5(-8 + z) 30 + 10z = (-8 * 5 + z * 5) 30 + 10z = (-40 + 5z) Solving 30 + 10z = -40 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 30 + 10z + -5z = -40 + 5z + -5z Combine like terms: 10z + -5z = 5z 30 + 5z = -40 + 5z + -5z Combine like terms: 5z + -5z = 0 30 + 5z = -40 + 0 30 + 5z = -40 Add '-30' to each side of the equation. 30 + -30 + 5z = -40 + -30 Combine like terms: 30 + -30 = 0 0 + 5z = -40 + -30 5z = -40 + -30 Combine like terms: -40 + -30 = -70 5z = -70 Divide each side by '5'. z = -14 Simplifying z = -14
| 5-(x+3)=10 | | -t+15=2 | | 3u+147=180 | | x(x+1)=1024 | | x=15+7x-81 | | -7+3+-5= | | 6x-19=10x-79 | | 10m=(3m-11)-17 | | -2x^3+19X^2-38x+21=0 | | z=2z-68 | | 3x-11=2(x-3)-8 | | -26+17= | | 1=-3xy | | 4t+5=2 | | 3(1-2x)=6-6x | | 16+-12+-7= | | x^2+X(c-b)+(c-a)(a-b)=0 | | 4x-90=3x-60 | | 5x+3y=56 | | abc-cba=973 | | -9x+1=-26 | | abc-cba=891 | | 4*sinx*cosx+2*cosx+1=0 | | abc-cba=675 | | 3a+7+2a=18-9 | | abc-cba=456 | | 15z-75=180 | | x-11=4x+44 | | 6(x-3)=2(3x-5) | | 4t-66=5t-87 | | sin(2x)+2*cosx+1=0 | | X^4-x^3-27x^2+25x+50=0 |